Analysis of the Effect of Vehicle Composition at Signalized Intersections on the Initial Loss Time of the Green Phase - Saputra, Yanuar Ardiansyah (Journal of Transportation Study Forum, 2024)
Cycle time consists of green time, yellow time, and red time. The green time of a phase is a function of the effective green time as well as the initial loss time and final gain time. There needs to be an approach to determine the value of the initial loss time at signalized intersections. There are several aspects that influence this, one of these aspects is the composition of vehicles at the intersection, this is because each vehicle has different acceleration variations in reaching normal speed conditions after stopping at the intersection. Analysis was carried out by observing video of traffic conditions at the Jl. Demak – Jl. Dupak, Surabaya on every approach. Observations were made on group vehicle behind line stop 12 m back until the group of vehicles exits the approach during the green phase, so that data on the composition of the vehicle group and the initial loss time that occurs for each green phase are obtained. The results of the analysis of the influence of vehicle composition on initial loss time using the vehicle group acceleration approach show that the initial loss time range that can occur is between 8.5 seconds to 14 seconds which is influenced by acceleration vehicle group.